Risk factors stratifying malignancy of nodules in contralateral thyroid lobe in patients with pre‐operative ultrasound indicated unilateral papillary thyroid carcinoma: A retrospective analysis from single centre. (24th November 2017) - Lv, Tian; Zhu, Changbin; Di, Zhongmin
Summary: Objective: Papillary thyroid carcinoma (PTC) is the most common thyroid carcinoma with a favourable clinical outcome. For unilateral PTC patients with thyroid nodules in the contralateral lobes, the necessity of total thyroidectomy (TT) is still in doubt. In this study, we aimed to define clinical factors that could be indicators for malignancy in nodules in the contralateral thyroid lobe, which could aid the clinician in selecting the appropriate operation approach. Design, Patients and Measurements: This is a retrospective study from January 2014 to December 2016 conducted in Shanghai Ruijin Hospital. A total of 1442 cases with unilateral PTC and ultrasonographically benign nodules in the contralateral lobe who underwent TT at a single institution were enrolled. All patients underwent pre‐operative ultrasonography (US), and all the cases were confirmed by board‐certified pathologists. Clinicopathological features such as age, gender, tumour location, tumour size, TgAb and TPOAb levels, capsular invasion, multifocality, central lymph node metastases and BRAF mutation were examined to evaluate the rate of malignancy in the contralateral thyroid nodules. Results: In total, 47% of patients (677 cases)were confirmed to have malignancy in the contralateral lobe. Univariant analysis indicated that capsular invasion, Hashimoto's thyroiditis, multifocal loci, central lymph node metastases as well as BRAF mutation predicted a high incidence of occult contralateral carcinoma. Multivariant analysis showed capsular invasion, multifocal ipsilateral thyroid lobe, central lymph node metastases as well as BRAF mutation can serve as independent predictors for malignancy in the contralateral thyroid lobe. Conclusions: Malignancy in the contralateral lobe was found in 47% of patients. This finding was associated with multifocal primary carcinomas involvement, capsular invasion, Hashimoto's thyroiditis history, central lymph node metastases and BRAF mutation, which should therefore be taken into consideration when planning therapeutic strategy for the patients.